2010
DOI: 10.1055/s-0030-1255591
|View full text |Cite
|
Sign up to set email alerts
|

The feasibility of endoscopic submucosal dissection for rectal carcinoid tumors: comparison with endoscopic mucosal resection

Abstract: This study suggests that ESD might be a feasible treatment technique for small rectal carcinoid tumors. It showed superior efficacy and comparable safety to EMR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
106
1
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 10 publications
8
106
1
2
Order By: Relevance
“…Moreover, a histologically complete resection was achieved for 96.6% (28/29) of the current series. This is important as a high rate of histologically complete resections with ESD may give several advantages for the treatment of foregut NETs [17][18][19] . First, a histologically complete resection …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a histologically complete resection was achieved for 96.6% (28/29) of the current series. This is important as a high rate of histologically complete resections with ESD may give several advantages for the treatment of foregut NETs [17][18][19] . First, a histologically complete resection …”
Section: Discussionmentioning
confidence: 99%
“…ESD has the advantage of a high probability of en bloc and histologically complete resection even in huge lesions because the technique involves dissection of the submucosal tissue beneath the lesion [14][15][16] . To date, the fact that ESD can facilitate a histologically complete resection of NETs has been verified for the use of ESD for treatment of rectal carcinoid tumors (now referred to as NETs) [17][18][19] . However, no systematic data have yet been published in which ESD has been applied to foregut NETs.…”
Section: Introductionmentioning
confidence: 99%
“…25 Several studies reported that ESD could be a feasible and safe procedure for treatment of carcinoid tumors showing good clinical outcomes. [34][35][36][37][38] Our study has several limitations. First, the study was a retrospective analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Some investigators have reported that conventional snare polypectomy or EMR resulted in unsatisfactory complete resection of colonic carcinoid tumors [27][28][29]. Lee et al stated that the positive resection vertical margin rate was 28.6% by EMR [15]. Concurrently, ESD has recently been reported to be useful for treating colorectal superficial tumors [12,13].…”
Section: Follow-up (Median; Month)mentioning
confidence: 99%
“…Concurrently, Endoscopic Submucosal Dissection (ESD), which enables en bloc resection regardless of tumor size, has recently been reported to be useful for treating colorectal superficial tumors [12][13][14]. There are many reports on the efficacy of ESD to treat colorectal carcinoids [15][16][17][18]. However, because ESD has the disadvantages of a high frequency of complications and need for advanced technical skills, this technique is not yet a standard treatment.…”
Section: Introductionmentioning
confidence: 99%